Pembagian Hak Waris Pada Asuransi Prudential Syariah Dalam Perspektif Hukum Kewarisan Islam - Ramadani, Mohammad Fadli; Susanti, Dyah Ochtorina (Acten Journal Law Review, 2024)
The purpose of journal is so that people who use sharia insurance policies can understand the inheritance system of Prudential Syariah Insurance according to Islamic Law. Inheritance law is a legal system that regulates the transfer of ownership of a deceased person to a person who has not died. Inheritance law is concluded as a system of regulating the assets of the heir which will be given by the heir's expert or rights with provisions in the form of consequences of being said to be an heir. In the Civil Code, inheritance law is not regulated in a special article, but the basic principle is contained in Article 830. The article states that inheritance only applies after death. Thus, the distribution of inherited wealth to heirs can only be done after the heir dies. Etymologically, sharia insurance in Arabic is called at-ta'min, the guarantor is called mu'ammin, while the insured is called mu'ammanah lahu or musta'min. While at-ta'min is taken from the word amana, because it means protection, tranquility, security, and freedom from fear. The type of research used in this study is Basic Research which is basically conducted only for the purpose of developing and reviewing existing theories using descriptive research methods. The results of the study show that the provisions of Islamic law are not violated in the inheritance system applied by the Prudential Syariah insurance branch in Surabaya, because in cases where customers experience a disaster, especially death, then Islamic insurance will provide the rights of heirs left by the testator (customer) as long as he follows the insurance. Keywords : Asurance; Islamic Law; Inheritance Law.